1998
DOI: 10.1088/0953-4075/31/7/004
|View full text |Cite
|
Sign up to set email alerts
|

The 2p interloper resonances in collisions

Abstract: Ab initio electron scattering calculations using the R-matrix approach have been performed for N + 2 within a three-state valence configuration-interaction model (VCI). The lowest three electronic target states (X 2 + u , A 2 u and the B 2 + u ) of this molecular nitrogen cation are included in the close-coupling method, with each state being represented by a valence CI approximation. From a detailed analysis of the resonance structure found in our work for the 1,3 + g symmetries we find four prominent Rydberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Orel et al (1990) calculated electronic impact cross-sections for the X 2 + g → B 2 + u transition at a single geometry using the complex-Kohn variational method. An R-matrix calculation by Ballance et al (1998) found Rydbergtype resonances of 1,3 + g symmetry, this work was extended by Nagy (Nagy et al 1999, Nagy 2003 to include vibrational motion to determine vibronic electron impact excitation crosssections for the X → B transition. These calculations are in the spirit of a conventional scattering calculation; a single or small number of appropriate geometries are calculated to determine a scattering parameter which, in general, only depends on these internuclear separations.…”
Section: Introductionmentioning
confidence: 99%
“…Orel et al (1990) calculated electronic impact cross-sections for the X 2 + g → B 2 + u transition at a single geometry using the complex-Kohn variational method. An R-matrix calculation by Ballance et al (1998) found Rydbergtype resonances of 1,3 + g symmetry, this work was extended by Nagy (Nagy et al 1999, Nagy 2003 to include vibrational motion to determine vibronic electron impact excitation crosssections for the X → B transition. These calculations are in the spirit of a conventional scattering calculation; a single or small number of appropriate geometries are calculated to determine a scattering parameter which, in general, only depends on these internuclear separations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, results of R-matrix method calculations were analysed recently by taking advantage of the known analytic forms of the R matrix and associated matrices when differentiating with respect to the energy [8][9][10] to find out the maximum of the Lorentzian form. This method was found useful for automatic and fast analysis of the results of R-matrix method calculations.…”
Section: Introductionmentioning
confidence: 99%
“…When the resonance is narrow or when the background S matrix depends only weakly on the energy, the resonance analysis is fairly simple, the results depending little on the choice of the analysis procedure among the ones mentioned so far. Indeed, the pure Lorentzian form of dδ(E)/dE reduces to a simple expression for the resonance position and width [8][9][10][11]. However, there are cases where the energy dependence of the background S matrix is far from negligible and plays a significant role.…”
Section: Introductionmentioning
confidence: 99%
“…At the valence CI level, an additional check on our results for the 1,3 + g scattering symmetry is a comparison of the lowest R-matrix pole with bound state calculations from closed-channel scattering calculations using the method of Seaton (1985), as implemented for molecules by Sarpal et al (1991) for a range of internuclear geometries which showed excellent agreement (Ballance et al 1998a). Electronic excitation from the ground X 2 + g state to both the A 2 u and B 2 + u states of N + 2 was then investigated within the fixed-nuclei approximation.…”
Section: Statementioning
confidence: 91%
“…The orbital set (2) yields 778 CSFs for the X state, 1308 CSFs for the A state and 778 CSFs for the B state with an increase in the computational complexity of the problem. To cater for nuclear motion effects in our work, calculations of cross sections for vibrational excitation of the ground state and vibronic excitation of the excited states (X-A, X-B transitions) are currently in progress within a non-adiabatic regime and the results from this work will be available in due course (Ballance et al 1998a).…”
Section: Statementioning
confidence: 99%